Modeling and process simulation of hollow fiber membrane reactor systems for propane dehydrogenation. Issue 10 (18th May 2017) - Choi, Seung‐Won; Sholl, David S.; Nair, Sankar; Moore, Jason S.; Liu, Yujun; Dixit, Ravindra S.; Pendergast, John G.
Abstract : We report a detailed modeling analysis of membrane reactor systems for propane dehydrogenation (PDH), by integrating a two‐dimensional (2‐D) nonisothermal model of a packed bed membrane reactor (PBMR) with ASPEN process simulations for the overall PDH plant including downstream separations processes. PBMRs based on ceramic hollow fiber membranes—with catalyst placement on the shell side—are found to be a viable route, whereas conventional tubular membranes are prohibitively expensive. The overall impact of the PBMR on the PDH plant (e.g., required dimensions, catalyst amount, overall energy use in reaction and downstream separation) is determined. Large savings in overall energy use and catalyst amounts can be achieved with an appropriate configuration of PBMR stages and optimal sweep/feed ratio. Overall, this work determines a viable design of a membrane reactor‐based PDH plant and shows the potential for miniaturized hollow‐fiber membrane reactors to achieve substantial savings. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4519–4531, 2017